2022
DOI: 10.1002/asia.202200879
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solutions of a Porous Host–Poly‐L‐lysine Complex with Information on Solids as Different Fluorescence by Guests

Abstract: N,N’‐Dipyrid‐3‐yl‐1,4,5,8‐naphthalenediimide linked to two tris(pentafluorophenyl)borane (1) exhibits strong fluorescence emission in the solid state by the formation of a charge‐transfer complex containing small aromatic guest molecules. Hydrophobic 1 was dissolved in water by mixing with poly‐L‐lysine (PLL) as a solubilizing agent. The 1‐PLL complex could include small aromatic guest molecules in water, significantly increasing the fluorescence. The fluorescence maxima of 1 in aqueous solution and solid stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…19,20 Previously, we succeeded in preparing aqueous solutions with information on solids (ASIS), such as aggregation-induced helical chirality in chiral crystals, 21 crystal polymorphism, 22 mechanochromic luminescence, and different uorescence maxima depending on the crystal polymorphism 22 or small aromatic guest molecules. 23 In these studies, natural polysaccharides or polypeptides were used as the solubilizing agents because of their excellent biocompatibility and biodegradability. [24][25][26] Therefore, RTP molecules in complexes with polysaccharides or polypeptides are expected to retain their phosphorescence properties in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Previously, we succeeded in preparing aqueous solutions with information on solids (ASIS), such as aggregation-induced helical chirality in chiral crystals, 21 crystal polymorphism, 22 mechanochromic luminescence, and different uorescence maxima depending on the crystal polymorphism 22 or small aromatic guest molecules. 23 In these studies, natural polysaccharides or polypeptides were used as the solubilizing agents because of their excellent biocompatibility and biodegradability. [24][25][26] Therefore, RTP molecules in complexes with polysaccharides or polypeptides are expected to retain their phosphorescence properties in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, polysaccharides and polypeptides can include a large amount and variety of guest molecules (Figure 1). [7][8][9][10][11][12][13] However, the preparation of complexes of CDxs, polysaccharides, and polypeptides with guest molecules via traditional solid-liquid extraction methods using sonication or heating requires long reaction times and affords aqueous solutions with relatively low concentrations of guest molecules. In contrast, these complexes can be rapidly and conveniently prepared using a mechanochemical high-speed vibration milling (HSVM) apparatus (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, these complexes can be rapidly and conveniently prepared using a mechanochemical high-speed vibration milling (HSVM) apparatus (Scheme 1a). [12][13][14] In this context, the incorporation of hydrophobic guest molecules in the lipid membrane of liposomes consisting of phospholipids (Figure 1) attracts considerable attention in the field of delivery systems. [15][16][17][18][19][20] Lipid-membrane-incorporated guest molecules (LMIGs) can be prepared using the organic solution injection method with a polar solvent such as methanol or dimethylsulfoxide (DMSO) or via a premixing method involving dissolution of lipids and guest molecules in an organic solvent followed by concentration and extraction with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Although the reason is not clear now, we reported that fluorescence maxima differ for crystals and powders or solid states and aqueous solutions when mixing with poly-L-lysine as a solubilizing agent. 12,30,38 Consequently, it was considered that the different molecular packing of 2 in a microenvironment may implicate the different fluorescence maxima.…”
mentioning
confidence: 99%